Association among self-esteem, aggression and psychological adjustment of orphans and family-reared children (Dhaka University Journal of Biological Sciences, 2020)
The present study explored the relationship among self-esteem, aggression, and psychological adjustment between orphan children and family-reared children. The sample comprised of 160 adolescents. Out of the total sample, 80 were living in the orphanages; and 80 participants were living with their both parents. They were selected by employing purposive-incidental sampling technique. Participants responded to the index of the Personal Information Form (PIF), Bangla version of Rosenberg Self-Esteem scale, Bangla version of Buss- Perry Aggression Questionnaire, and Bangla version of Adolescent Personality Assessment Questionnaire. Results showed that key variables were significantly correlated with one another. Results indicated that the children in orphanages have lower self-esteem, are more aggressive, and have higher psychological adjustment problem than children living with their both parents. Results also showed that girls have lower self-esteem and they are less aggressive than boys. Self-esteem has been found to be an important predictor of psychological adjustment of the respondents. Therefore, the findings of present research will encourage our perceptive of self-esteem and will advance the understanding about the negative impact of aggression on children’s mental health.Dhaka Univ. J. Biol. Sci. 29(1): 97-105, 2020 (January)